2008
DOI: 10.1577/t07-222.1
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression between Fall‐ and Spring‐Run Chinook Salmon Assessed by Long Serial Analysis of Gene Expression

Abstract: Abstract.-Of all Pacific salmonids, Chinook salmon Oncorhynchus tshawytscha display the greatest variability in return times to freshwater. The molecular mechanisms of these differential return times have not been well described. Current methods, such as long serial analysis of gene expression (LongSAGE) and microarrays, allow gene expression to be analyzed for thousands of genes simultaneously. To investigate whether differential gene expression is observed between falland spring-run Chinook salmon from Calif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Seven MOR genes, n24 , asor , and two ependymin ‐ like genes were significantly upregulated (1.5–2.5×), and olfc13.1 and O51F2 HUMAN —a novel salmonid gene—were downregulated (0.7–0.5×) in prespawning individuals. Bernier et al () also found elevated ependymin levels in the brains of returning adult Chinook salmon. Our data confirm the downregulation of olfc13.1 and asor1 in adults, whereas ependymin levels were similar in adults and juveniles.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Seven MOR genes, n24 , asor , and two ependymin ‐ like genes were significantly upregulated (1.5–2.5×), and olfc13.1 and O51F2 HUMAN —a novel salmonid gene—were downregulated (0.7–0.5×) in prespawning individuals. Bernier et al () also found elevated ependymin levels in the brains of returning adult Chinook salmon. Our data confirm the downregulation of olfc13.1 and asor1 in adults, whereas ependymin levels were similar in adults and juveniles.…”
Section: Discussionmentioning
confidence: 87%
“…GST (Kudo et al, 1999) and UGT (Lazard et al, 1991) are detoxification enzymes that may be involved in neuromodulation and in termination of odor signaling by degrading/conjugating odorant molecules (Hino et al, 2009). Ependymin is a neurotrophic factor, which has long been thought of as an effector of long-term memory consolidation in fish (Bernier, Birkeland, Cipriano, McArthur, & Banks, 2008;Lado et al, 2013). It was upregulated in fall-run mature chinook salmon (O. tshawytscha) compared with spring-run and ocean-dwelling fish and was suggested to have a role in memory formation in homing salmon (Bernier et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of haplotype composition, overall genetic diversity, and differentiation (based on both exact tests and φ ST ) indicate more similarity to the sample of contemporary fall Chinook salmon than to those in the contemporary tributaries used for redirection, particularly to the Chinook salmon from Priest Rapids Hatchery. Genetic components have been indicated for functional life history differences, including run timing in Chinook salmon [ 108 111 ]. However, to our knowledge, no functional associations have been made for control region haplotypes, or for mtDNA in general, in Chinook salmon.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby ependymin is hypothesized to be involved in the retrieval of olfactory imprinting memory, once retained as juvenile migrating downstream from their natal stream to the ocean. Also in fall- and spring-run Chinook salmon, ependymin exhibited much higher expression levels than in an individual from the ocean [ 41 ]. Recently, ependymin (in this case the ependymin II precursor) was shown to play an important role as neural mediator in the olfactory processing of sex pheromones in the telencephalon of goldfish [ 42 ].…”
Section: Discussionmentioning
confidence: 99%